2009
DOI: 10.1007/s10637-009-9233-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase IB trial of oral talactoferrin in the treatment of patients with metastatic solid tumors

Abstract: Purpose: We evaluated safety and activity of talactoferrin, a novel immunomodulatory protein in a phase IB trial of patients with refractory solid tumors. Methods: Thirty-six patients with metastatic cancer who had progressed on, or were ineligible for, standard chemotherapy received single-agent oral talactoferrin. Following doseescalation, with no DLTs , patients were randomized to 4.5 or 9 g/day talactoferrin. Results: Talactoferrin was well tolerated with apparent anti-cancer activity, particularly in NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Apart from its main physiological functions, namely binding and transport of iron ions, Lf exhibits antiviral, antimicrobial, antiprotozoal and antioxidant activities. Moreover, recombinant Lf has been tested for clinical use in treatment and prevention of such human and animal diseases as solid tumors (Hayes et al, 2005(Hayes et al, , 2010 and diarrhea (Humphrey et al, 2002). Pepsin digestion of Lf generates its fragment lactoferricin (Bellamy et al, 1992) that also reveals potent bactericidal activity against antibiotic-resistant strains of Staphylococcus aureus and Escherichia coli from clinical origins (Flores-Villaseñor et al, 2010).…”
Section: Characteristics Of the Key Functions Of Lactoferrinmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from its main physiological functions, namely binding and transport of iron ions, Lf exhibits antiviral, antimicrobial, antiprotozoal and antioxidant activities. Moreover, recombinant Lf has been tested for clinical use in treatment and prevention of such human and animal diseases as solid tumors (Hayes et al, 2005(Hayes et al, , 2010 and diarrhea (Humphrey et al, 2002). Pepsin digestion of Lf generates its fragment lactoferricin (Bellamy et al, 1992) that also reveals potent bactericidal activity against antibiotic-resistant strains of Staphylococcus aureus and Escherichia coli from clinical origins (Flores-Villaseñor et al, 2010).…”
Section: Characteristics Of the Key Functions Of Lactoferrinmentioning
confidence: 99%
“…Pepsin digestion of Lf generates its fragment lactoferricin (Bellamy et al, 1992) that also reveals potent bactericidal activity against antibiotic-resistant strains of Staphylococcus aureus and Escherichia coli from clinical origins (Flores-Villaseñor et al, 2010). Moreover, recombinant Lf has been tested for clinical use in treatment and prevention of such human and animal diseases as solid tumors (Hayes et al, 2005(Hayes et al, , 2010 and diarrhea (Humphrey et al, 2002). Its use as vaccine adjuvant modulates the adaptive immune response in humans (Hwang et al, 2011).…”
Section: Characteristics Of the Key Functions Of Lactoferrinmentioning
confidence: 99%
See 1 more Smart Citation
“…In a followup phase IB trial, TLf was again well-tolerated by patients with metastatic cancer. NSCLC patients (n=12) experienced 87% relative reduction in TGR and renal cell carcinoma (RCC) patients (n = 7) experienced a 98% relative reduction in TGR [84]. In a phase 2 clinical trial of TLf in RCC, Jonasch et al [85] reported that TLf given at a dose of 1.5 g twice daily (12 weeks on, 2 weeks off) resulted in no toxicities to 44 patients with RCC, 6.4 months mPFS, 21.1 months median overall survival, and a 77% 1-year survival rate.…”
Section: Lactoferrin and Lactoferricinmentioning
confidence: 99%
“…In a phase IB trial [13] and a follow-on phase II study [14], 16 patients with metastatic RCC, all with documented tumor progression during the 9 months prior to enrollment, were treated at our institution with single-agent oral talactoferrin. Patients received oral rhLF in amounts of 4.5 grams or 9 grams per day administered in two divided doses.…”
Section: Introductionmentioning
confidence: 99%